Using Qualitative Comparative Analysis (QCA) to determine the barriers of municipal associationism in Colombia - Tutistar-Rosero, Diana Ximena; Pinazo-Dallenbach, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this paper is to point some of the causes that explain the low levels of municipal associationism the departments of Colombia show. By the means of a QCA (Qualitative Comparative Analysis), different causal configurations that explain this phenomenon are presented. The data used comes from the National Planning Department of Colombia. The outcome has been calculated by the proportion of municipalities of each department that belong to some type of association, taking as reference the Territorial Association Schemes. Among the conclusions that emerge, it is interesting to highlight that the combination of low levels in four of the five conditions analyzed (urbanization, quality of life, economic activity and safety), leads to lower levels of municipal associationism. Likewise, institutional capacity does not seem to explain the phenomenon studied.